Subchronic Toxicity Test of Cincalok Oil Towards Wistar Rats Haematology - Nugraha, Fajar; Kurniawan, Hadi; Fajriaty, Inarah; Nurbaeti, Siti Nani; Goh, Sri Wahyuni (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Cincalok is a fermented shrimp product which has the potential to be used as pharmaceutical preparations. Its LD50 showed non-toxic. However, subchronic toxicity tests have not been performed. Therefore, this study aims to determine its subchronic toxicity assay towards haematology in male and female white rats in the Wistar strain. The animals used were divided into six groups, the control group induced with virgin coconut oil (VCO), the dose group induced with Cincalok oil (100, 400, 1000 mg/kg BW), and two satellite groups (control group VCO and 1000 mg/kg BW). Haematological parameters evaluated include hemoglobin, Red Blood Cell Count (RBC), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), Mean Corpuscular Hemoglobin Concentration (MCHC), leukocytes, basophils, lymphocytes, eosinophils, platelets, and neutrophils. The average level of haematological profile in this study indicated that hemoglobin, MCH, MCHC, basophils, eosinophils, stem neutrophils, neutrophil segments, lymphocytes, and monocytes platelets in female and male rats were still in the normal range.While, there was a decrease in levels below the normal range in the parameters of RBC, leukocytes, MCV and hematocrit. It was concluded that the consumption of cincalok oil orally had no effect in hemoglobin, RBC, MCV, MCH, MCHC, leukocytes, basophils, lymphocytes, eosinophils, platelets, and neutrophil.